Conflitos socioambientais: uma proposta de investigação-ação à luz da educação ambiental dialógico-problematizadora - Silva, Lucicléia Pereira da (2016)
The main objective of this thesis was to develop theoretical and methodological foundations of environmental education, dialogical-problematizing perspective. The research was based on the theoretical framework that articulates research-action, Freire's pedagogy and empowerment (empowerment), being conducted in the qualitative mode, in collaboration with the Ecomuseum of the Amazon Program (EAP) and Home-School of Fisheries (HSF), linked to Foundation Bosque School (Funbosque), located on the island of Caratateua, Belém PA. The proposal was aimed at promoting greater integration between themes: citizenship, culture, environment and community-based tourism "Heritage Program and Training of Local Development Actors" performed by EAP, as well as the strengthening of the empowerment process in field of environmental education of high school students (EJA mode) integrated into the Technical course in Fisheries Resources of HSF. Research-action took place around environmental conflicts related to fisheries, being involved in the process: 4 technicians and 1 volunteer EAP, 1 professor of HSF (former coach of the EAP), 1 pedagogical coordinator of HSF and 28 young and school adults. We emphasize that students mostly belong to the local population in the region of the islands of Belém and Barcarena, Pará municipalities. The methodology followed the steps of Lewinian spiral of action-research, based on the survey of the problem through pre-diagnosis followed by planning-action-evaluation-reflection. To prepare the corpus (empirical data), diverse techniques were adopted: report analysis, semi-structured interviews, filming and questionnaires. As a contribution to the corpus analysis adopt the discursive semiotics, content analysis and descriptive statistics. The results achieved with regard to the EAP demonstrated a breakthrough by changing the design of environmental education linked to the conservative side, that directed only towards changing behavior and attitudes related to environmental protection, to the dialogical problematical aspect, classified by technical the EAP and educational coordinator of HSF as Innovative, Academic Way, Practice, Positive / Effective and Structure/ Manufacturing. We emphasize that the proposal its foundations integrated planning between the themes of the EAP. As for the empowerment process of the HSF students, the achieved results showed strong evidence that began to be developed in the field of Freire's approach, there is indicative of awareness and development of a critical faculty making among students. Thus, we conclude that this action research, conducted in a participatory and democratic manner, articulated the assumptions of Paulo Freire contributed to promote changes in educational practice within the technical course which resulted in knowledge gains and critical thinking by students. We also conclude that the discursive semiotics allowed to capture this transformation, making it a valuable tool for evaluating the process of making of consciousness.